2011
DOI: 10.1099/jmm.0.029959-0
|View full text |Cite
|
Sign up to set email alerts
|

Generation and evaluation of A2-expressing Lactococcus lactis live vaccines against Leishmania donovani in BALB/c mice

Abstract: Leishmaniasis is a parasitic disease affecting over 12 million individuals worldwide. As current treatments are insufficient, the development of an effective vaccine is a priority. This study generated and assessed the efficacy of Leishmania vaccines engineered from the non-colonizing, non-pathogenic Gram-positive bacterium Lactococcus lactis. A truncated, codon-optimized version of the A2 antigen from Leishmania donovani was engineered for expression in Lactococcus lactis in three different subcellular compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…In addition, L. lactis is noninvasive and thus has less potential to trigger immune system hyper-activation or side effects from prolonged use [27], [28]. Currently, L. lactis -based vaccines have not been evaluated under clinical trials, however, successful vaccinations have been reported using L. lactis -based genetically modified micro-organisms (GMO) [29] bacterial vaccines against several diseases in mice model [14], [30], [31]. In the present study, we found that L. lactis vaccines via oral administration were well accepted by NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, L. lactis is noninvasive and thus has less potential to trigger immune system hyper-activation or side effects from prolonged use [27], [28]. Currently, L. lactis -based vaccines have not been evaluated under clinical trials, however, successful vaccinations have been reported using L. lactis -based genetically modified micro-organisms (GMO) [29] bacterial vaccines against several diseases in mice model [14], [30], [31]. In the present study, we found that L. lactis vaccines via oral administration were well accepted by NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that subcutaneous immunization with L. lactis expressing tetanus toxin fragment C (TTFC) anchored to the cell-wall was more immunogenic than immunization with bacteria expressing the antigen in the cytoplasm or secreted, and was able to provide better protection against lethal challenge. Additionally, our group previously showed that subcutaneous immunization with L. lactis expressing A2 anchored to the cell-wall induced the highest level of antigen-specific antibody titers compared to other expression strategies and reduced parasite burdens in L. donovani -challenged animals [29]. Therefore, we hypothesized that for subcutaneous immunization with L. lactis , the expression of the antigen anchored to the cell-wall would be the most immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity results in reduced lesion size and numbers of parasites in protected animals [73][74][75][76][77][78]. Given the impressive reductions in parasite burdens at the site of infection and in distant body sites, anti-A2 immune responses may act by promoting clearance of parasites instead of only preventing their dissemination.…”
Section: Formulations Of A2 Vaccine: Aiming Induction Of a Prominent mentioning
confidence: 97%
“…Several pre-clinical tests, which included administration of A2 antigens either as recombinant protein associated to different adjuvants [73,74], DNA [75,76], attenuated nonreplicative viruses [30], non-pathogenic bacteria [77] or non-virulent parasites (L. tarentolae) [78], have provided evidence of the protective effect of vaccination in mice.…”
Section: Formulations Of A2 Vaccine: Aiming Induction Of a Prominent mentioning
confidence: 99%